2021
DOI: 10.1101/2021.07.16.452676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic regulator genes direct lineage switching in MLL-AF4 leukaemia

Abstract: The fusion gene MLL-AF4 defines a high-risk subtype of pro-B acute lymphoblastic leukaemia. However, relapse can be associated with a switch from acute lymphoblastic to acute myeloid leukaemia. Here we show that these myeloid relapses share oncogene fusion breakpoints with their matched lymphoid presentations and can originate in either early, multipotent progenitors or committed B-cell precursors. Lineage switching is linked to substantial changes in chromatin accessibility and rewiring of transcriptional pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…This mechanism is probably connected to gene mutations at the antigen locus due to immune pressure by CAR-T cells 114 . Lineage switch is linked to substantial changes in chromatin accessibility and rewiring of transcriptional programs in tumor cells, including alternative splicing 115 . Antigen-low escape indicated that CAR-T cells targeting specific antigens were unable to effectively eliminate specific antigens-low cells 116 .…”
Section: The Intricate Network Sustaining Immunosuppression In Timementioning
confidence: 99%
“…This mechanism is probably connected to gene mutations at the antigen locus due to immune pressure by CAR-T cells 114 . Lineage switch is linked to substantial changes in chromatin accessibility and rewiring of transcriptional programs in tumor cells, including alternative splicing 115 . Antigen-low escape indicated that CAR-T cells targeting specific antigens were unable to effectively eliminate specific antigens-low cells 116 .…”
Section: The Intricate Network Sustaining Immunosuppression In Timementioning
confidence: 99%